The Morphosyntax of Middle Voice in Uab Meto - Naniana N. Benu; Risman Iye; Asriani Abbas (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
This study focused on middle voice in Uab Meto. The point of this study is to describe the morphosyntactic element of the middle voice in Uab Meto. There are three forms of middle voice constructions in Uab Meto, namely reflexive, reciprocal, and lexical. A subject-reflective enclitic demonstrates the middle's reflexivity. Ma-, which is usually linked to the verb, signifies reciprocity. es nok es